Can the meson cloud explain the nucleon strangeness? - Carvalho, Fabiana [UNESP]; Navarra, Fernando S.; Nielsen, Marina (American Physical Society (APS), 2005)
We use a version of the meson cloud model, including the kaon and the K* contributions, to estimate the electric and magnetic strange form factors of the nucleon. We compare our results with the recent measurements of the strange quark contribution to parity-violating asymmetries in the forward G0 electron-proton scattering experiment. We conclude that it is very important to determine experimentally the electric and magnetic strange form factors, and not only the combination GEs+ηGMs, if one does really intend to understand the strangeness of the nucleon. © 2005 The American Physical Society.